Предмет: Математика, автор: HeTyHukaXa

M-(5/6m+1/4m) при m=16 m=7/37

Ответы

Автор ответа: PoLerka
0
16 - ( frac{5}{6m}  frac{1}{4m} ) =
16 - ( frac{40}{3} +  frac{6}{4} ) =
16 - ( frac{160}{12} +  frac{18}{12} ) =
16 -  frac{89}{6} =
 frac{96}{6}  frac{89}{6} =
 frac{7}{6}  1frac{1}{6}

 frac{7}{37} ( frac{5}{6m}  frac{1}{4m} ) =
 frac{7}{37} - ( frac{70}{44}  frac{21}{444} ) = 
 frac{7}{37}  frac{91}{444} =
 frac{168}{888}  frac{182}{888}
 frac{14}{888}  frac{7}{444}
Автор ответа: PoLerka
0
 frac{7}{37} - ( frac{70}{444} +  frac{21}{444} ) =
Похожие вопросы